Implementasi Sistem Informasi dalam Diplomasi Militer Terhadap Pengambilan Keputusan Strategis - Arief Hidayat,; Yotanabey A.M,; Ahmad G. Dohamid, (Nusantara Journal of Information and Library Studies (N-JILS), 2025)
The Ten-Dash Line represents China's unilateral territorial claim over the South China Sea. Indonesia is firmly defending its sovereignty while prioritizing peaceful diplomatic efforts to resolve the conflict in the Natuna Sea. Diplomacy employs military diplomacy or defense diplomacy. The success of a country's defense diplomacy strategy is the collaboration of diplomacy, defense, and development components integrated within an information system. In the complex and sensitive context of the South China Sea conflict, decision-making requires accurate, timely, and up-to-date information to formulate effective policies. The research method used was a qualitative case study approach. Data were obtained through interviews and literature review. The results illustrate that the role of information systems is increasingly crucial in supporting the implementation of effective military diplomacy. Meanwhile, information systems as a support for military diplomacy are not yet optimal because each data center and information center within the Ministry of Defense and within the Indonesian National Armed Forces (TNI) are not fully integrated. Hedging methods are decided based on in-depth analysis obtained from information systems. However, without interoperability, considerable time and resources are spent addressing system differences, thereby reducing the overall effectiveness and efficiency of implementing military diplomacy strategies. To achieve the full potential of information systems, ongoing investment in technology development, personnel training, and increased inter-agency collaboration is required.